2007
DOI: 10.1177/0148558x0702200103
|View full text |Cite
|
Sign up to set email alerts
|

Cost Behavior and Fundamental Analysis of SG&A Costs

Abstract: Downloaded from 2. If the stochastic process is assumed to be AR(1) instead of random walk, then a weighted where p is the first-order serial correlation, would be the appropri- =&A,,, =&At,,-,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(150 citation statements)
references
References 25 publications
7
133
0
10
Order By: Relevance
“…In another related research, Anderson et al [2007] estimate an earnings prediction model and find that future earnings are positively related to changes in the SG&A cost ratio in periods when revenue declines, inconsistent with the traditional interpretation of SG&A cost changes.…”
Section: Hypothesesmentioning
confidence: 91%
See 2 more Smart Citations
“…In another related research, Anderson et al [2007] estimate an earnings prediction model and find that future earnings are positively related to changes in the SG&A cost ratio in periods when revenue declines, inconsistent with the traditional interpretation of SG&A cost changes.…”
Section: Hypothesesmentioning
confidence: 91%
“…Our study addresses this issue by focusing on the understanding of cost behavior patterns by financial analysts and extends Anderson et al [2007] by exploring whether investors are misled by analysts.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study integrated a typical management accounting research topic, cost behavior, with three standard financial accounting topics. Anderson et al (2007) estimated an earnings prediction model and reported that future earnings were positively associated with changes in the SG&A cost ratio in periods in which revenue declines, inconsistent with traditional interpretation of SG&A cost changes. In addition, in their survey, abnormal positive returns could be earned on portfolios formed by going long on firms with high increases in the SG&A cost ratio…”
Section: Introductionmentioning
confidence: 91%
“…Sehingga dimungkinkan manajer akan mempertahankan sumber daya yang tidak terpakai. Menurut Anderson et al (2006), perilaku biaya administrasi dan umum dapat dipelajari dengan menghubungkan aktivitas penjualan karena volume penjualan memiliki pengaruh pada beberapa komponen biaya penjualan, administrasi dan umum. Ketika manajemen memutuskan untuk mempertahankan utilisasi sebenarnya menunda penyesuaian biaya, yang pada akhirnya membiarkan biaya penjualan, administrasi dan umum tetap.…”
Section: Sticky Cost Pada Biaya Penjualan Administrasi and Umumunclassified